2014
DOI: 10.15249/7-1-33
|View full text |Cite
|
Sign up to set email alerts
|

Accountability challenges in public–private partnerships from a South African perspective

Abstract: One of the potential benefits of public-private partnerships (PPPs) is its capacity to enhance accountability. Although the South African government has made several efforts to address the need for fairness in service delivery and improve accountability in procurement, accountability remains a challenge in PPPs in South Africa and most other countries. If PPPs are to play their role in infrastructure development and service delivery, and thus serve public interests, the problem of accountability must be addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The empirical findings showed very few corporations report PPP activities in their annual reports. South Africa’s PPP projects have been considered by the World Bank as the most successful in sub-Saharan Africa (Thomson, 2005); however, the study by Fombad (2013) showed that disclosure of information on these projects is weak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The empirical findings showed very few corporations report PPP activities in their annual reports. South Africa’s PPP projects have been considered by the World Bank as the most successful in sub-Saharan Africa (Thomson, 2005); however, the study by Fombad (2013) showed that disclosure of information on these projects is weak.…”
Section: Literature Reviewmentioning
confidence: 99%
“…South Africa followed a global trend in the popularity of PPPs by establishing a more formal PPP structure within the National Treasury in 1999 [ 24 ]. Although there were PPPs prior to this date, these arrangements did not follow a standardised process or receive formal recognition as PPPs within the treasury.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, there has been a trail of criticisms about the alienation of key stakeholders in the PPP procurement process. For example, in South Africa, the process has been said to be ‘riddled with corrupt practises in what has become known as tenderpreneurship’ ( Fombad, 2013 : 11). The selection process for PPPs must be seen to be fair by all parties involved.…”
Section: Creating An Enabling Environment For Private Sector Investme...mentioning
confidence: 99%